PEMBANGUNAN DESTINASI PARIWISATA YANG BEKELANJUTAN MELALUI PENERAPAN NILAI-NILAI ERGONOMI - Ni Made Eka Mahadewi; Ni Ketut Dewi Irwanti (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
The development of tourism can not only refer to attractions, accessibility and destination facilities. However, the values of structuring in each tourist attraction in a destination are important to note. And along with various tourism developments, the comfort factor is one of the important factors that determine the decision of tourists to visit a tourist destination. Many things affect the comfort of tourists while in a tourist destination. One of the approaches used to make tourists comfortable using the infrastructure, facilities, tourist activities, and services provided is to implement the ergonomic approach that seeks for people to be healthy, safe, comfortable, effective and efficient so that they are more productive and the quality of life is better also they got happiness and sustainable.